Sífilis congênita, escolaridade materna e cuidado pré-natal no Pará entre 2010 e 2020: um estudo descritivo - SILVA, Jean Marcos Souza da (2023)
Syphilis is an infectious disease caused by a spirochete, Treponema pallidum, whose transmission occurs through sexual contact and transplacentally (vertical transmission). Congenital syphilis is the consequence of the dissemination of Treponema pallidum via the hematogenous route, from the infected mother not treated or inadequately treated during pregnancy to the fetus. By analyzing the educational level of a population, it is possible to indirectly infer their income conditions, access to health services, as well as eating, hygienic and behavioral habits. Schooling presents socioeconomic conditions, which can be seen as determinants of health and well-being. Quality and humanized prenatal care is essential for maternal and neonatal health. Care for pregnant women should include attitudes of prevention and health promotion, in addition to the diagnosis and adequate treatment of any problems that arise during this period. The objective is to describe the epidemiological profile of congenital syphilis in the period from 2010 to 2020 in the state of Pará and to relate maternal conditions such as schooling, completion or non-performance of prenatal care and the evolution of confirmed cases. This is a cross-sectional, with a descriptive design and using a quantitative approach. The data collected refer to the incidence of congenital syphilis in the state of Pará, located in the North region of Brazil, from 2010 to 2020. The number of confirmed and reported cases of congenital syphilis in Pará, from 2010 to 2020, totaled 7,170 cases. When observing the data on the mother's education, 24.4% (1,754) had not completed elementary school II (fifth to eighth grade). The unknown/blank value for maternal education corresponded to 26.4% (1896) of the sample. Prenatal care was performed by 84.5% (6,058) of the mothers and not performed by 12.8% (920), ignored/white 2.7% (192). Prenatal care is an important tool for the prevention and control of congenital syphilis, and its control is classified as an indicator of the quality of prenatal care, according to the Ministry of Health (MS). In Pará, most cases had ignored maternal schooling (26.4%) and mothers who had not completed the fifth to eighth grade corresponded to 24.4%. The deficiency in the notification system becomes visible, due to the high degree of underreporting in relation to the mothers' education.